Social mapping as a methodological resource for heritage analysis. Mapping experiences in Miramar (Córdoba, Argentina) - Martin Silva, Valeria Belén; Zabala, Mariela Eleonora; Fabra, Mariana (Universidad Pedagógica y Tecnológica de Colombia, 2019)
We presented a reflection on Social Cartography as a theoretical-methodological participatory research proposal for the study, assessment and integral management of the archaeological heritage, based on a field work experience in the town of Miramar from Ansenuza (Córdoba, Argentina). In which we apply the technique of collective mapping, establishing a dialogue between museum workers, residents, tourists and researchers on heritage, from a collaborative and transdisciplinary perspective, to analyze the opportunities and challenges offered by Social Cartography to address the relations between communities on heritage and territory. It is concluded that based on the critical and participatory cartographic practices carried out, new ways of understanding the inhabited space have emerged, which give priority to the feeling of the local community in the construction of the local cultural landscape. In this sense, it seeks to provide new methodological strategies for heritage research.